Preparation method and application of all-solid-state cross-linked polymer electrolyte

The all-solid lithium battery electrolyte material with cross-linked network structure was prepared by rapid cross-linking and solution casting method, which solved the problems of high crystallinity, low ion conductivity, and low lithium ion migration at room temperature, and achieved battery performance and improve security.

CN119481300APending Publication Date: 2025-02-18CHINA NAT PETROLEUM CORP

Patent Information

Application Number
CN202310992194.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The solid electrolyte materials of existing all-solid-state lithium batteries have high crystallinity, low ion conductivity, low lithium ion migration number, and easy oxidation and decomposition at room temperature, which affect the cycle life and safety of the battery.

Method used

The method of rapid crosslinking and solution casting is used to prepare all-solid polymer electrolyte membranes with crosslinked network structures. By introducing amino segments that can form hydrogen bonds with polyether segments, the effect between ether-based oxygen atoms and lithium ions is reduced. , increase the number of lithium ion migration and avoid the introduction of impurities through click reaction.

Benefits of technology

The mechanical strength of the electrolyte and the number of lithium ion migrations are improved, the circulation performance and safety of the battery are enhanced, and the cost and production complexity of the battery are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481300A_ABST
    Figure CN119481300A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an all-solid-state cross-linked polymer electrolyte, which comprises the following steps: dissolving polyethyleneimine in a solvent, and stirring for the first time to obtain a first solution; quickly adding lithium salt into the first solution, and stirring for the second time to obtain a second solution; adding polyethylene glycol diglycidyl ether into the second solution, and stirring for 6 hours to obtain a cross-linked polymer electrolyte solution; and pouring the cross-linked polymer electrolyte solution on a polyfluortetraethylene plate, and drying to obtain the all-solid-state cross-linked polymer electrolyte. The all-solid-state polymer electrolyte membrane with a cross-linked network structure is prepared by adopting a rapid cross-linking and solution casting method, the reaction condition is mild, the efficiency is high, and the mechanical strength of the electrolyte is improved; besides, the reaction principle is based on the click reaction of amino and epoxy group, no catalyst, initiator and other impurities need to be introduced, the product is directly obtained from reactants, the reaction is thorough, the system is pure, and potential adverse effects on battery circulation are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a preparation method and application of an all-solid-state cross-linked polymer electrolyte. Background Art

[0002] Secondary lithium-ion batteries have been widely used in the fields of new power system energy storage and power batteries. However, the electrolyte used in commercial lithium-ion batteries at this stage is a flammable organic electrolyte, which will burn or explode when subjected to mechanical shock or thermal runaway, causing serious safety accidents. The new all-solid-state lithium battery uses solid electrolytes to replace the flammable liquid components in traditional lithium batteries, fundamentally solving the safety hazards caused by organic electrolytes, and is regarded as a weather vane for the future development of lithium-ion batteries.

[0003] Solid electrolyte is the core of all-solid-state lithium battery and plays a decisive role in battery performance. Polymer membrane materials (polyethers) have the advantages of high salt dissolution, good ductility, and soft texture, and have the potential for large-scale production. However, polyethers (such as polyethylene oxide PEO) currently used for solid electrolytes also face the problems of high room temperature crystallinity, resulting in low ion conductivity; too strong complexation between ether oxygen atoms and lithium ions, resulting in low lithium ion migration number; easy oxidation and decomposition under high pressure, resulting in material loss and accumulation of by-products in the cycle, affecting the battery cycle life. Copolymerizing and cross-linking polyethers with polymers rich in other functional groups can effectively improve the performance of cross-linked polymer membrane materials. CN114373995A blends boron nitride nanopowder, g-C3N4, PEO, and PVDF to obtain a composite solid polymer electrolyte. However, the polyether electrolyte obtained by simple blending is still a linear structure, with insufficient mechanical strength and easy to be pierced by lithium dendrites formed during battery cycle; the dispersed nanofillers such as boron nitride and g-C3N4 are easy to agglomerate, and the improvement of the electrochemical performance of solid polymer electrolyte is not obvious; at the same time, the problem of easy oxidation and decomposition of polyether under high pressure has not been significantly improved. CN114163589A uses esterified PEO to initiate the copolymerization of perfluoroalkylethyl methacrylate to obtain a solid block polymer electrolyte, but the esterification reaction process of PEO is difficult to control and the cost is high; the concentration of copper salt used in the polymerization reaction is high and difficult to remove, and as an impurity, it has a potential impact on the battery cycle; at the same time, the interaction between the fluorine-containing segment and the polyether segment is weak, and the improvement of the lithium ion migration number is not significant, which affects the battery cycle performance.

[0004] Therefore, developing an all-solid-state lithium battery cross-linked polymer electrolyte material with excellent performance and capable of rapid and large-scale preparation has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a fully solid cross-linked polymer electrolyte to solve the above technical problems.

[0006] To achieve the above object, the present invention provides a method for preparing an all-solid-state cross-linked polymer electrolyte, the method comprising:

[0007] Dissolving polyethyleneimine in a solvent to obtain a first solution by first stirring;

[0008] Rapidly adding lithium salt to the first solution, and obtaining a second solution by a second stirring;

[0009] Adding polyethylene glycol diglycidyl ether to the second solution and stirring for 6 hours to obtain a cross-linked polymer electrolyte solution;

[0010] The cross-linked polymer electrolyte solution is poured onto a polytetrafluoroethylene plate, and after drying, a fully solid cross-linked polymer electrolyte is obtained.

[0011] Optionally, the number average molecular weight of the polyethyleneimine is 600-60000.

[0012] Optionally, the solvent includes one of the following: methanol, ethanol, acetonitrile, acetone and tetrahydrofuran.

[0013] Optionally, the lithium salt includes one of the following: lithium bis(trifluoromethanesulfonyl imide), lithium bis(difluorosulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate and lithium perchlorate.

[0014] Optionally, the molar amount of lithium ions in the lithium salt is 1-20 times the molar amount of primary amino groups in polyethyleneimine.

[0015] Optionally, the molar amount of the ether group in the polyethylene glycol diglycidyl ether is 1-10 times the molar amount of the primary amino group in the polyethylene imine.

[0016] Optionally, the number average molecular weight of the polyethylene glycol diglycidyl ether is 400-1200.

[0017] Optionally, the first stirring time is 4 hours, and the second stirring time is 2 hours.

[0018] Optionally, the cross-linked polymer electrolyte solution is cast on a polytetrafluoroethylene plate and dried to obtain a fully solid cross-linked polymer electrolyte, comprising:

[0019] The polytetrafluoroethylene plate cast with the cross-linked polymer electrolyte solution is placed in a 60° C. forced air drying oven for 4 hours;

[0020] The polytetrafluoroethylene plate was taken out and placed in a vacuum drying oven at 50° C. for 24 hours to obtain a fully solid cross-linked polymer electrolyte.

[0021] The invention also provides an application of the all-solid cross-linked polymer electrolyte in a battery.

[0022] Technical effects and advantages of the present invention:

[0023] The invention provides a method for preparing a fully solid cross-linked polymer electrolyte, the method comprising: dissolving polyethyleneimine in a solvent, and obtaining a first solution by a first stirring; quickly adding a lithium salt into the first solution, and obtaining a second solution by a second stirring; adding polyethylene glycol diglycidyl ether into the second solution, and obtaining a cross-linked polymer electrolyte solution after stirring for 6 hours; and pouring the cross-linked polymer electrolyte solution on a polytetrafluoroethylene plate, and obtaining a fully solid cross-linked polymer electrolyte after drying.

[0024] The present invention adopts a method of rapid cross-linking and solution casting to prepare an all-solid-state polymer electrolyte membrane with a cross-linked network structure. The reaction conditions are mild, the efficiency is high, the steps are simple and fast, and the mechanical strength of the electrolyte is improved. At the same time, an amino segment that can form a hydrogen bond interaction with a polyether segment is introduced, which reduces the interaction between the ether oxygen atom and the lithium ion and increases the lithium ion migration number of the system. In addition, the reaction principle is based on the click reaction of amino and epoxy groups, and there is no need to introduce any impurities such as catalysts and initiators. The product is directly obtained from the reactants, the reaction is thorough, the system is pure, and there is no potential adverse effect on the battery cycle.

[0025] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a flow chart of the preparation method of the all-solid-state cross-linked polymer electrolyte. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings provided by the present invention, and the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportional relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.

[0029] In order to solve the problems of low conductivity, poor stability and easy penetration by lithium dendrites of solid polymer electrolyte materials, the present invention provides a method for preparing a fully solid cross-linked polymer electrolyte, the method comprising: dissolving polyethyleneimine in a solvent, and obtaining a first solution by a first stirring; quickly adding a lithium salt to the first solution, and obtaining a second solution by a second stirring; adding polyethylene glycol diglycidyl ether to the second solution, and obtaining a cross-linked polymer electrolyte solution after stirring for 6 hours; and casting the cross-linked polymer electrolyte solution on a polytetrafluoroethylene plate, and obtaining a fully solid cross-linked polymer electrolyte after drying.

[0030] The present invention adopts a method of rapid cross-linking and solution casting to prepare an all-solid-state polymer electrolyte membrane with a cross-linked network structure. The reaction conditions are mild, the efficiency is high, the steps are simple and fast, and the mechanical strength of the electrolyte is improved. At the same time, an amino segment that can form a hydrogen bond interaction with a polyether segment is introduced, which reduces the interaction between the ether oxygen atom and the lithium ion and increases the lithium ion migration number of the system. In addition, the reaction principle is based on the click reaction of amino and epoxy groups, and there is no need to introduce any impurities such as catalysts and initiators. The product is directly obtained from the reactants, the reaction is thorough, the system is pure, and there is no potential adverse effect on the battery cycle.

[0031] In order to better understand this method, the following Figure 1 The preparation method of all-solid-state cross-linked polymer electrolyte is introduced in detail.

[0032] Step 1: dissolving polyethyleneimine in a solvent at room temperature, and obtaining a first solution by first stirring.

[0033] The number average molecular weight of polyethyleneimine is 600-60000, and the solvent is one of methanol, ethanol, acetonitrile, acetone and tetrahydrofuran.

[0034] Among them, the first stirring time is 4h.

[0035] Step 2: quickly add lithium salt into the first solution, and obtain a second solution by stirring for the second time.

[0036] The lithium salt is one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(difluorosulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, and lithium perchlorate, and the molar amount of lithium ions is 1-20 times the molar amount of primary amino groups in polyethyleneimine.

[0037] The second stirring time is 2 h.

[0038] Step 3: Add polyethylene glycol diglycidyl ether to the second solution and stir for 6 hours to obtain a cross-linked polymer electrolyte solution.

[0039] The number average molecular weight of polyethylene glycol diglycidyl ether is 400-1200, and the molar amount of the ether group is 1-10 times the molar amount of the primary amino group in polyethylene imine.

[0040] Step 4: pouring the cross-linked polymer electrolyte solution onto a polytetrafluoroethylene plate, and obtaining a fully solid cross-linked polymer electrolyte after drying.

[0041] Specifically, the cross-linked polymer electrolyte solution is cast on a flat polytetrafluoroethylene plate and placed in a 60°C forced air drying oven for pre-drying for 4 hours; the polytetrafluoroethylene plate is taken out and further dried in a vacuum drying oven at 50°C for 24 hours to obtain a fully solid cross-linked polymer electrolyte material.

[0042] In order to better illustrate the scheme, examples and comparative examples are provided below.

[0043] Example 1

[0044] 1) Dissolve 0.5 g of polyethyleneimine in methanol at room temperature and stir for 4 h;

[0045] 2) Weigh 0.8 g of lithium perchlorate, quickly add it into the above polyethyleneimine solution, and stir for 2 h;

[0046] 3) adding 2 g of polyethylene glycol diglycidyl ether to the above solution and stirring for 6 h to form a cross-linked polymer electrolyte solution;

[0047] 4) Cast the above solution on a flat polytetrafluoroethylene plate and pre-dry it in a 60°C forced air drying oven for 4 hours;

[0048] 5) Take out the polytetrafluoroethylene plate and continue drying it in a vacuum drying oven at 50° C. for 24 h to obtain a fully solid cross-linked polymer electrolyte material.

[0049] The obtained cross-linked polymer membrane material for the solid electrolyte of an all-solid-state lithium battery is a polyethyleneimine-polyethylene glycol block polymer containing lithium perchlorate, and the specific component is LiClO4-PEI-PEG. The obtained cross-linked polymer electrolyte material is used as the electrolyte of an all-solid-state lithium battery to prepare a button battery, and the capacity retention rate is 67% after 500 cycles at a rate of 0.2C.

[0050] Example 2

[0051] 1) Dissolve 0.3 g of polyethyleneimine in tetrahydrofuran at room temperature and stir for 4 h;

[0052] 2) Weigh 0.6 g of lithium bis(trifluoromethanesulfonyl)imide, quickly add it into the above polyethyleneimine solution, and stir for 2 h;

[0053] 3) adding 2.5 g of polyethylene glycol diglycidyl ether to the above solution and stirring for 6 h to form a cross-linked polymer electrolyte solution;

[0054] 4) Cast the above solution on a flat polytetrafluoroethylene plate and pre-dry it in a 60°C forced air drying oven for 4 hours;

[0055] 5) Take out the polytetrafluoroethylene plate and continue drying it in a vacuum drying oven at 50° C. for 24 h to obtain a fully solid cross-linked polymer electrolyte material.

[0056] The obtained cross-linked polymer membrane material for the solid electrolyte of all-solid-state lithium battery is a polyethyleneimine-polyethylene glycol block polymer containing lithium bis(trifluoromethanesulfonyl)imide, and the specific component is LiTFSI-PEI-PEG. The obtained cross-linked polymer electrolyte material is used as the electrolyte of the all-solid-state lithium battery to prepare a button battery, and the capacity retention rate is 72% after 500 cycles at a rate of 0.2C.

[0057] Example 3

[0058] 1) Dissolve 0.7 g of branched polyethyleneimine in acetonitrile at room temperature and stir for 4 h;

[0059] 2) Weigh 0.5 g of lithium bis(oxalatoborate) and quickly add it to the polyethyleneimine solution and stir for 2 h;

[0060] 3) adding 2.8 g of polyethylene glycol diglycidyl ether to the above solution and stirring for 6 h to form a cross-linked polymer electrolyte solution;

[0061] 4) Cast the above solution on a flat polytetrafluoroethylene plate and pre-dry it in a 60°C forced air drying oven for 4 hours;

[0062] 5) Take out the polytetrafluoroethylene plate and continue drying it in a vacuum drying oven at 50° C. for 24 h to obtain a fully solid cross-linked polymer electrolyte material.

[0063] The obtained cross-linked polymer membrane material for the solid electrolyte of an all-solid-state lithium battery is a polyethyleneimine-polyethylene glycol block polymer containing lithium bis(oxalatoborate), and the specific component is LiBOB-HPEI-PEG. The obtained cross-linked polymer electrolyte material is used as the electrolyte of an all-solid-state lithium battery to prepare a button battery, and the capacity retention rate is 78% after 500 cycles at a rate of 0.2C.

[0064] Comparative Example 1

[0065] The main difference between Comparative Example 1 and Example 1 is that polyethyleneimine is not added in step 1.

[0066] The preparation method of Comparative Example 1 ultimately failed to obtain a solid electrolyte membrane.

[0067] Comparative Example 2

[0068] The main difference between Comparative Example 2 and Example 1 is that the stirring is only performed for 0.5 h after adding polyethylene glycol diglycidyl ether in step 3.

[0069] The membrane material finally obtained by the preparation method of Comparative Example 2 is semi-solid and viscous, and a fully solid electrolyte membrane cannot be obtained.

[0070] Comparative Example 3

[0071] The main difference between Comparative Example 3 and Example 1 is that the amount of lithium perchlorate added in step 2 is 0.2 g.

[0072] The preparation method of Comparative Example 3 finally obtained an all-solid-state electrolyte membrane. The obtained all-solid-state electrolyte membrane material was used as the electrolyte of an all-solid-state lithium battery to prepare a button battery. After 500 cycles at a rate of 0.2C, the capacity retention rate was 15%, which was much lower than that of Example 1.

[0073] Comparative Example 4

[0074] The main difference between Comparative Example 4 and Example 1 is that the amount of polyethylene glycol diglycidyl ether added in step 3 is 8 g.

[0075] The material finally obtained by the preparation method of Comparative Example 4 is very hard and it is impossible to obtain a membrane material with ductility.

[0076] The invention also provides an application of the all-solid cross-linked polymer electrolyte in a battery.

[0077] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fully solid cross-linked polymer electrolyte, characterized in that: The method comprises: Dissolving polyethyleneimine in a solvent to obtain a first solution by first stirring; Rapidly adding lithium salt to the first solution, and obtaining a second solution by a second stirring; Adding polyethylene glycol diglycidyl ether to the second solution and stirring for 6 hours to obtain a cross-linked polymer electrolyte solution; The cross-linked polymer electrolyte solution is poured onto a polytetrafluoroethylene plate, and after drying, a fully solid cross-linked polymer electrolyte is obtained.

2. The method according to claim 1, characterized in that The number average molecular weight of the polyethyleneimine is 600-60000.

3. The method according to claim 1, characterized in that: The solvent includes one of the following: methanol, ethanol, acetonitrile, acetone and tetrahydrofuran.

4. The method according to claim 1, characterized in that The lithium salt includes one of the following: lithium bis(trifluoromethanesulfonyl imide), lithium bis(difluorosulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate and lithium perchlorate.

5. The method according to claim 1, characterized in that The molar amount of lithium ions in the lithium salt is 1-20 times the molar amount of primary amino groups in polyethyleneimine.

6. The method according to claim 1, characterized in that The molar amount of the ether group in the polyethylene glycol diglycidyl ether is 1-10 times the molar amount of the primary amino group in the polyethylene imine.

7. The method according to claim 1, characterized in that The number average molecular weight of the polyethylene glycol diglycidyl ether is 400-1200.

8. The method according to claim 1, characterized in that: The first stirring time is 4 hours, and the second stirring time is 2 hours.

9. The method according to claim 1, characterized in that: The cross-linked polymer electrolyte solution is poured onto a polytetrafluoroethylene plate and dried to obtain a fully solid cross-linked polymer electrolyte, comprising: The polytetrafluoroethylene plate cast with the cross-linked polymer electrolyte solution is placed in a 60° C. forced air drying oven for 4 hours; The polytetrafluoroethylene plate was taken out and placed in a vacuum drying oven at 50° C. for 24 hours to obtain a fully solid cross-linked polymer electrolyte.

10. Use of the all-solid cross-linked polymer electrolyte prepared by the method according to any one of claims 1 to 9 in a battery.

Citation Information

Patent Citations

  • Block polymer and preparation method thereof, block polymer electrolyte and preparation method thereof, and polymer lithium battery

    CN114163589A

  • Composite solid polymer electrolyte and preparation method thereof

    CN114373995A

Cited By

  • In-situ lithium-supplementing positive electrode material and preparation method thereof

    CN120072946A